Humanistic Approach In Education According To Paulo Freire - Fauzan Akmal Firdaus; Akrim Mariyat (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
Education has an important and strategic role to ensure the development of cognitive intelligence, psychomotor and affective. Education aims to develop human potential and forms a good personality. However, current education loses humane aspects (dehumanization). This is due to the approach used for teaching based on the educator (teacher center) and not centered on learners (student center). The ultimate purpose of humanistic approach in education is the learning process that was started and is intended for the benefit of humanizing mankind. Humanizing humans, is to achieve self-actualization, self-understanding, and self-realization people to learn optimally. The concept of humanistic approach in education according to Freire is a process of liberation from the oppressive system and raised awareness of the critical processes centered on educators and learners as subjects in the process of teaching and learning. The implication of humanistic approach in education is how to educators to encourage students to think critically and act according to the values of humanity. Since then, the humanistic approach in education should be applied in the process of learning and teaching in order to produce a good learner and critical of reality.